Afro-Indo-America: Between the sacred and the profane - Ravenna, Roberto; Meliciani , Francesco; Granado, Alberto; Portuondo, Inaury (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
The material depicts spaces and objects of research focused on Afro-American culture. The term corresponds to the plural territory baptized as "The Indies" by European ignominy and that in contemporaneity has been circumscribed to South American segments omitting other universes. However, land borders appear as a result of the colonizing conquest itself, and multiple narratives are translated that break through these barriers. From the value of culture, the weak line between sacred space and the surrounding Latin American real world is exposed. A process that has sustained since its genesis the cultural persistence among the dissimilar native groups, those brought from Africa and other parts of the world. The most up-to-date conception emphasizes rituality, orality, festivities and identity processes marked by the phenomenon of inter-American migration with an irrefutable Afro matrix. Likewise, the native peoples are a common axis throughout the transatlantic geography, the central reason in each of the interventions that can be seen in this audiovisual. Prestigious Cuban researchers and young people dominate this exhibition, shedding new light on universal culture.